Electroanalytical adaptation of the classical Ellman's Assay: Determination of total thiols in incubation media from a biological sample (excised articular cartilage) - Nekrassova, O; Lawrence, N; Lee, R; Urban, J; Compton, R (2003)
The total thiols in a medium containing authentic biological sample (articular cartilage) has been determined electrochemically. The detection strategy utilises the electrochemical adaptation of the Ellman's reaction process via the electrochemically initiated reaction of thiols with diethyl-p-phenylenediamine. The strategy has been examined over a biologically significant pH range and the behaviour observed rationalised. The detection of thiols within the biological sample is shown to proceed with micromolar levels of thiol determined within the sample.